Acute non‐ambulatory tetraparesis in a 6‐month‐old Standardbred weanling caused by a cervical vertebral epidural haematoma. (28th February 2020) - MacMillan, K.; Bourque, A.; Perry, L.; Stoughton, W.
Summary: A 6‐month‐old Standardbred weanling presented with acute non‐ambulatory tetraparesis. Cranial nerve examination was normal and neuroanatomic localisation suggested there was a focal C1‐C5 spinal cord lesion. Post‐mortem examination identified a cervical vertebral epidural haematoma at the level of C2‐C3 causing spinal cord compression and neurological deficits. Histological examination determined the haematoma was several weeks old making the lesion chronic. Since the clinical progression was acute, this suggests an acute on chronic pathophysiology. Even with no history of trauma, an epidural haematoma should be on the differential list in young horses with acute tetraparesis.